Environmental Biology of Fishes - Environmental Biology of Fishes (Springer Nature, 2026)
Environmental Biology of Fishes is an international journal that publishes original studies on the ecology, life history, epigenetics, behavior, physiology, morphology, systematics and evolution of marine and freshwater fishes. Empirical and theoretical papers are published that deal with the relationship between fishes and their external and internal environment, whether natural or unnatural. The journal concentrates on papers that advance the scholarly understanding of life and draw on a variety of disciplines in reaching this understanding. Papers focusing on cartilaginous fishes are particularly welcome, in keeping with the journal’s expanded aim to serve as the leading venue for studies on the environmental biology of sharks, skates, and rays to complement those on the diversity of other marine and freshwater fishes.
FI 0.51
Q3
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Biología marina; Ecología; Ciclo de vida